When "College and Career Ready" Means Only (or Mostly) College Ready: Perspectives From Stakeholders in Six Rural and Small Communities. Issue 4 (2nd October 2021) - Budge, Kathleen; Wargo, Elizabeth; Carr-Chellman, Davin; Canfield-Davis, Kathy
ABSTRACT: This study of rural stakeholders' perspectives related to college and career readiness exposes a nuanced dynamic that extends beyond pragmatic concerns for preparing rural students for the future. As college preparatory courses "crowded out" Career and Technical Education (CTE) offerings, stakeholders voiced a concomitant sense of losing something they described as real-life, relevant, and rural. Viewing extra-local policy as deforming local schooling and disembedding it from the community, stakeholders in the six rural and small school districts studied appear to be confined by three forms of binary thinking in their effort to provide a rural-responsive education.